(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study investigates the impact of culture shock on employee morale in the Indian IT sector, with particular emphasis on the mediating role of emotional labour. While previous research has examined culture shock in relation to job satisfaction and performance, this paper highlights morale as a broader indicator of employee well-being.A descriptive–analytical design was adopted. Data were collected from 430 early-career IT employees across 57 NASSCOM-listed firms in South India. Validated scales measured organisational climate, self-efficacy, role ambiguity, emotional labour, and employee morale. Confirmatory Factor Analysis (CFA), Structural Equation Modelling (SEM), and bootstrapping techniques were used to test the hypothesised direct and mediating effects.The results confirmed the reliability and validity of the constructs, with the CFA showing a good model fit. SEM revealed that organisational climate, self-efficacy, and role ambiguity significantly impacted morale, with role ambiguity being the strongest predictor. Mediation analysis showed emotional labour partially mediated these effects. All hypotheses were supported, confirming that culture shock influences morale directly and indirectly.